High-Performance Distributed Objects over a System Area Network - Forin, Alessandro; Hunt, Galen; Li, Li; Wang, Yi-Min (Proceedings of the 3rd USENIX Windows NT Symposium, 1999)
The availability of high-speed user-level networking interfaces has shifted the performance bottleneck to the distributed-object infrastructures. In this paper, we describe an approach to building high-performance, commercial distributed object systems over system area networks (SANs) with user-level networking. The specific platforms that we use in this study are the Virtual Interface Architecture (VIA) and Microsoft’s Distributed Component Object Model (DCOM). We give a detailed functional and performance analysis of DCOM and apply optimizations at several layers to take full advantage of modern high-speed networks, while still preserving the full set of DCOM features including security and different threading models. Through extensive runtime and transport optimization, our system achieves a round-trip latency of 72 microseconds for null DCOM calls, more than 5 times faster than the current implementation on the same network. By eliminating buffer copying at the marshaling layer, our system achieves an application bandwidth of 86.1 megabytes per second, more than 7 times improvement over the current implementation.